Prostaglandin levels in seminal plasma and sperm extracts of the domestic turkey, and the effects of cyclooxygenase inhibitors on sperm mobility - Thurston Ronald J; Korn Nancy; Kennedy Jessica H (BMC, 2003)
Abstract Background Turkey reproduction is by artificial insemination using pooled semen so there is interest in storing semen. Fertilizing capacity declines after six hours storage, possibly due to poor sperm mobility. Prostaglandins (PG) affect mammalian sperm motility, but avian sperm has not been widely studied. For this study, levels of PG E1, E2, and F2 alpha in turkey seminal plasma and sperm extract, and effects of cyclooxygenase (COX) inhibitors on sperm mobility were determined. Methods Seminal Plasma and sperm extract PG E1, E2, and F2 alpha, from 1.0 mL pooled semen, were measured by ELISA. In Trial 1, PG were determined from 122 wk old toms (n = 4). Trial 2 used 36 wk old toms (n = 7). For Trial 3, PGE2 only was measured from 48 wk (n = 6) and 154 wk old toms (n = 3). The effects of non-specific COX inhibitors indomethacin, diclofenac, tolmetin, or aspirin (n = 10), or specific COX-1 or COX-2 inhibitors (n = 3) on sperm mobility were measured (Accudenz swim-down test). Results Seminal plasma PG (pg/mL) in Trials 1 and 2, respectively, were 185.2 ± 88.4 and 187.2 ± 33.7 for PGE1; 141.4 ± 43.1 and 100.4 ± 14.6 for PGF2 alpha; and 431.0 ± 155.1 for PGE2 (Trial 1 only). Sperm extract PG (pg/10 billion cells) in Trials 1 and 2, respectively, were 215.1 ± 38.1 and 208.9 ± 41.5 for PGE1; 133.7 ± 51.7 and 49.8 ± 8.3 for PGF2 alpha; and 52.3 ± 8.6 for PGE2 (Trial 1 only). In Trial 3, seminal plasma PGE2 (pg/mL) in older versus younger males was 1097.9 ± 99.3 versus 853.2 ± 144.6 and sperm extract PGE2 (pg/10 billion cells) was 208.0 ± 56.1 versus 102.4 ± 14.8. Cyclooxygenase inhibitors (0.001 to 10 mM) decreased sperm mobility: indomethacin 15 to 100%; diclofenac 4 to 100%; tolmetin 27 to 74%; aspirin (tested at 0.01 to 15 mM) 22 to 42%; resveratrol (COX-1) and NS-398 (COX-2), both tested at 0.1 to 10 mM, 38 to 98% and 44 to 85%, respectively. Conclusion These results indicate that PG are present in turkey seminal plasma and sperm, and COX inhibitors decrease turkey sperm mobility.